Retornos e alternativas de entrega de última milha: um estudo sobre produtos financeiros tangíveis no Brasil - Okada, Camila Yukari (Universidade Federal de São Carlos, 2020)
The increasing number of last mile delivery due to the growth of electronic commerce involved several challenges and, consequently, the increase in home delivery failures generating parcel returns. The objective of this article is to study the main causes of returns and alternatives presented in the literature that best suits the case of tangible financial products of a banking company in Brazil to all involved parts of the operation, the emission company, the intermediate operator, and the end customer. Tangible financial products such as credit and debit cards are characterized by their small size and the high rate of missed deliveries. As case study, it was confronted the perception of three groups related with the process: the clients, the intermediate operators, and the issuing company. Based on the literature review, several factors may be related to home deliveries failures for this type of product, such as lack of security, urban infrastructure challenges, and operational failures. With the alternatives identified, all the parties involved to the financial product last mile delivery will be then confronted regarding the feasibility of the alternatives for delivering. The obtained results showed that the alternative that best suits the case is Pick-Up Point that attend the main factors elected, the security, the product’s state of conservation, and the delivery time. To conclude, a group of members from the issuing company considered the proposed alternative was suitable, with modifications, according to the company’s reality
Last mile delivery returns and alternatives: a case study of financial goods in Brazil
Keywords: Entrega em domicílio; Falha de entrega; Logística de cartões; Home delivery; Failed delivery; Logistics of bank cards; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO